2015
DOI: 10.1002/ep.12093
|View full text |Cite
|
Sign up to set email alerts
|

Online monitoring of Fenton‐mediated reactive red 6B oxidation kinetics

Abstract: Online spectrophotometric technology was used to monitor the Fenton oxidation of the model dye Reactive Red 6B (RR6B) in an aqueous solution. The results showed that online monitoring technology was well equipped to record detailed information during the Fenton process. RR6B was successfully decomposed by Fenton oxidation and it was determined that optimal experimental conditions yielded nearly 100% dye removal to be 3.5 3 10 25 M ferrous ion, 2.5 3 10 23 M hydrogen peroxide and 3.85 pH. Both firstorder and Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Finally, as the Fenton process adhered to firstorder kinetics (30)(31)(32), the last term in Eq. (9) (10) is the apparent reaction rate constant.…”
Section: Dep Degradation Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, as the Fenton process adhered to firstorder kinetics (30)(31)(32), the last term in Eq. (9) (10) is the apparent reaction rate constant.…”
Section: Dep Degradation Kineticsmentioning
confidence: 99%
“…BMG model was derived from Behnajady, Modirsshahla and Ghanbary (33), which effectively predicted degradation of Direct Blue 71, azo dye RR6B and Acid Red 66 by Fenton process (30,34,35). BMG kinetic model could be expressed as follows (30):…”
Section: Dep Degradation Kineticsmentioning
confidence: 99%
“…Data obtained from the experiment were tested using three kinetic models, first order, second order, and BMG kinetic model. Some researchers have reported that the BMG model has effectively predicted degradation of the Fenton process [20,24,34]. By applying the equations in Table 1 below, the three kinetic models at different [H 2 O 2 ] to [COD] ratios during the 15 min Fenton reaction were calculated.…”
Section: Kinetic Of Cod Degradationmentioning
confidence: 99%
“…For Equations (10)-(12), C 0 and Ct are showing COD concentration (mg/L) of sugarcane vinasse at initial (t = 0) and time t (min), respectively; k 1 is first order kinetic parameter (min −1 ); k 2 is second order kinetic parameter (L·mg −1 ·min −1 ); m (min) and b are two characteristic constants of BMG kinetic model which represent the relation between oxidation capacity and reaction kinetics. predicted degradation of the Fenton process [20,24,34]. By applying the equations in Table 1 below, the three kinetic models at different [H2O2] to [COD] ratios during the 15 min Fenton reaction were calculated.…”
Section: Kinetic Model Equationmentioning
confidence: 99%
“…is a powerful oxidant (oxidation potential = 2.8 eV) that can effectively degrade organic pollutants such as textile dyes . Various AOPs such as photocatalysis , Fenton oxidation , sonolysis electrochemical oxidation and hybrid processes have been investigated for the treatment of textile effluents.…”
Section: Introductionmentioning
confidence: 99%